Chekhov’s moral code - Smolkin, M. (Literatūra, 1970)
The study of Chekhov’s moral code is interesting in many respects. It shows the deep connection between Chekhov’s ethical personality and his works and gives the opportunity of penetrating into Chekhov’s writings from the point of view of his individuality, which he was very anxious about. Free from didactics and moralization, Chekhov’s creative work in the profundity of its imagery contains the profound ethical principles. The article covers the genesis of Chekhov’s moral code and reveals the essence of any single principle. Having brought up a personality of himself, Chekhov wanted to bring up his reader as a man too. He begins his pedagogical experiment in his family, extending it to the audience of his readers. When comparing Tolstoy’s and Chekhov’s principles of life, one not only discovers the likeness in their aspiration for moral height and purity, but the distinction between the moral maximalism of Tolstoy and Chekhov’s simple principles of morality as well. Chekhov considered the moral code to be common for the whole of mankind.